Effects of naphthalene on gene transcription in Calanus finmarchicus (Crustacea: Copepoda) - Hansen, Bjørn Henrik; Altin, Dag; Vang, Siv-Hege; Nordtug, Trond; Olsen, Anders J. (Aquatic toxicology, 2008)
The planktonic copepod Calanus finmarchicus is a key species in the Northern Atlantic food web; an oceanic area with extensive oil production. Naphthalene is one of the major constituents of produced water and water soluble fractions of petrogenic oils. This study investigates the effects on gene transcription of a short term exposure to naphthalene at levels well below LC 50 concentrations. This was done in order to establish a molecular basis of naphthalene toxicity in a species which has previously been subject only to very limited studies at the molecular level. Naphthalene exposure to C. finmarchicus was found to cause glutathione S-transferase (GST) induction, indicating lipid peroxidation as the major mode of naphthalene toxicity. There is no clear evidence that the putative cytochrome P450 enzymes CYP1A2 and CYP330A1 mRNAs are parts of a detoxification enzyme system. Instead, an observed decrease in CYP330A1 mRNA levels at the highest naphthalene exposure concentration may indicate an effect on ecdysteroidogenesis. Only the lowest naphthalene concentration lead to increased mRNA levels of antioxidants SOD and CAT, indicating no clear evidence for general cellular oxidative stress following exposure. Small and insignificant changes in the HSP-70, HSP-90 and ubiquitin mRNA levels indicate a small degree of protein damage owing to naphthalene exposure. The established culture of C. finmarchicus at the SINTEF/NTNU Sealab, and the use of gene transcription analyses provide excellent tools for improving the understanding of biochemical mechanisms involved in the defense against environmental impacts and the molecular modes of toxicity in this species.